Haemorrhagic fever in Rio Grande do Sul: leptospirosis as the primary diagnosis - Mariana S. Adam; Janete Aparecida Machado; Marcelo Carneiro; Beanir S. Lara; Terezinha Kreibich (Universidade de Santa Cruz do Sul, 2011)
.